2012
DOI: 10.1177/1358863x12453938
|View full text |Cite
|
Sign up to set email alerts
|

Association of the smoothelin (SMTN) gene with cerebral infarction in men: A haplotype-based case–control study

Abstract: Smoothelin is a specific type of cytoskeletal protein found in smooth muscle cells (SMCs). Several previous research studies have examined the relationship between smoothelin and atherosclerotic plaque. The aim of the present study was to further assess the association between the human SMTN gene and cerebral infarction (CI) using a haplotypebased case-control study. A total of 168 CI patients and 259 supercontrols were genotyped for the five single-nucleotide polymorphisms (SNPs) used as genetic markers for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A loss of expression of both SMTN A and SMTN B in mice is lethal at a young age, and an SMTN B deficiency results in a decreased contractile potential of SMCs, hypertension and cardiac hypertrophy. , In humans, the SMTN gene is associated with essential hypertension, cerebral infarction, and myocardial infarction. A loss of SMTN B results in the disappearance of the contractile VSMC phenotype in a variety of vascular disorders . Although SMTN has been used as a marker for the highly differentiated SMC, and SMTN expression is useful in studying vascular malformation and injury, its function has not been well studied, presumably due to the difficulty to prepare soluble material for biochemical analysis .…”
Section: Discussionmentioning
confidence: 99%
“…A loss of expression of both SMTN A and SMTN B in mice is lethal at a young age, and an SMTN B deficiency results in a decreased contractile potential of SMCs, hypertension and cardiac hypertrophy. , In humans, the SMTN gene is associated with essential hypertension, cerebral infarction, and myocardial infarction. A loss of SMTN B results in the disappearance of the contractile VSMC phenotype in a variety of vascular disorders . Although SMTN has been used as a marker for the highly differentiated SMC, and SMTN expression is useful in studying vascular malformation and injury, its function has not been well studied, presumably due to the difficulty to prepare soluble material for biochemical analysis .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the SmtnB specific knockout mouse has been used to demonstrate a role for the vascular form of SMTN in the development of hypertension. More recently, genetic association studies with human patient populations have found a link between SmtnB haplotypes and essential hypertension , cerebral infarct and myocardial infarct .…”
Section: The Smoothelin Family Of Smooth Muscle Proteinsmentioning
confidence: 99%